PENGGUNAAN PROTOTIPE KERAN WUDU OTOMATIS MENGGUNAKAN ARDUINO DAN MULTI SENSOR UNTUK KONSERVASI AIR - Abdul Wahid, Mulyadi; Vazilla, Vebri; Rohendi, Aulia (Lingkar: Journal of Environmental Engineering, 2023)
Generally, the volume of water used for wudu varies for each person, with an average of 6 liters per person per time, depending on the habit of how one opens the tap and the water flow rate. However, according to hadith, the Prophet Muhammad Saw performed wudu using only one mud of water (625 milliliters). Water conservation during wudu can be achieved by reducing the amount of water discharged from the tap. In this study, an automatic wudu faucet prototype was designed, equipped with infrared sensors, a buzzer, ultrasonic technology, and controlled by an Arduino Uno microcontroller. In this system, the faucet will only open when there is an object or a hand/foot beneath it and will close when no object is detected anymore. Additionally, the system will produce a sound indicating that an object is approaching within a distance of 10 cm. This prototype is able to increase the efficiency of water usage during wudu by 67%. The average water usage for wudu using a manual faucet by the subjects was found to be 4.86 liters per person per time. After using the automatic wudu faucet prototype, the average water usage was reduced to 1.624 liters per person per time. Water conservation, even in small activities like wudu, can contribute to preserving water resources and ensuring their availability on Earth.